1991
DOI: 10.1128/jb.173.2.842-850.1991
|View full text |Cite
|
Sign up to set email alerts
|

Telomeric and dispersed repeat sequences in Candida yeasts and their use in strain identification

Abstract: Several different repetitive DNA sequences have been isolated from the pathogenic yeast Candida albicans. These include two families of large dispersed repeat sequences (Ca3, Ca24) and a short (23-bp) tandemly repeated element (Ca7) associated with C. albicans telomeres. In addition, a large subtelomeric repeat (WOL17) has been cloned. DNA fragments containing the telomeric repeats are highly variable among different C. albicans strains. We have shown that the Ca3 repeat is relatively more stable and is suitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
132
0
4

Year Published

1993
1993
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(137 citation statements)
references
References 45 publications
(40 reference statements)
1
132
0
4
Order By: Relevance
“…Molecular Basis of Genome Fingerprinting with Ca3, 27A, and RPS Ca3 (Sadhu et al 1991), 27A (Scherer and Stevens 1988), and RPS (Iwaguchi et al 1992a) probes have been used as tools for epidemiological analysis of C. albicans infections. When genomic Southern blots of various strains are probed with any of these sequences, restriction fragment-length polymorphisms are found (Pujol et al 1997).…”
Section: Natural Aneuploidy In Candida Albicansmentioning
confidence: 99%
“…Molecular Basis of Genome Fingerprinting with Ca3, 27A, and RPS Ca3 (Sadhu et al 1991), 27A (Scherer and Stevens 1988), and RPS (Iwaguchi et al 1992a) probes have been used as tools for epidemiological analysis of C. albicans infections. When genomic Southern blots of various strains are probed with any of these sequences, restriction fragment-length polymorphisms are found (Pujol et al 1997).…”
Section: Natural Aneuploidy In Candida Albicansmentioning
confidence: 99%
“…Southern blot hybridization of total cellular DNA from the mutants and their parental strains with the C. albicans-specific mid-repeat sequence Ca3 (Sadhu et al, 1991) was performed. Genomic DNA was digested with EcoRI (New England Biolabs).…”
Section: Isolation Of Colony Form Mutantsmentioning
confidence: 99%
“…The mutants and their putative parents were analysed by Southern blot hybridization of total cellular DNA with the C. albicans-specific mid-repeat sequence Ca3 (Sadhu et at., 1991). The results established that the germinationdeficient mutants had arisen from the parents indicated in Table 1 (data not shown).…”
Section: Establishment Of the Identity Of Clinical Isolates And The Fmentioning
confidence: 99%
“…Thus, we named the 5259 bp fragment, the sequence in which the RPS portion was excluded from the 6 kbp fragment, as HOK. A homology search using the FASTA program revealed a high degree of homology with the B fragment of Ca3, which has frequently been used as a molecular epidemiological probe (Sadhu et al, 1991;Anderson et al, 1993). Most of the B fragment was included in HOK.…”
Section: Sequencing Analysis and A New Conserved Sequence Hokmentioning
confidence: 99%
“…The Ca3 molecular epidemiological probe developed by D. R. Soll's group (Sadhu et al, 1991) contains both the RPS-and the HOK-related sequences. We have confirmed that the hybridization patterns of the RPS and of HOK are different from each other (Figs 1 and 2).…”
Section: Conservation Of Thementioning
confidence: 99%